Physicochemical properties of rambutan seed fat / Nadya Hajar [et al.] - Mohamad, Naemaa; Tokiman, Azlin; Abdul Rahim, Hasvenda; Munawar, Nursabrina; Sani, Najihah; Mayuddin, Fathin Khairunnisa; Azman, Noorrashikin; Nosarimy, Illiyina Syafinaz; Md Yatim, Noor Shahirah; Abd Rashid, Mohamad Iqmal; Shahrizan, Nur Shahieerah (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Rambutan (Nephelium lappaceum L.) fruit is abundantly present in Malaysia. It is a seasonal fruit that present twice a year. It has short shelf life at ambient temperature has contributed to fruit wastage. Thus, the initiative of producing canned rambutan is an innovation that makes rambutan fruit available throughout the year. The canned rambutan industry leaves large amount of rambutan seed. This study focused on utililization of rambutan seed as valuable product which is Rambutan Seed Fat (RSF). The RSF was extracted using Soxhlet Extraction method for 8 hours. The objective of this study was to determine the physicochemical properties of RSF: melting point (°C), Refractive Index (RI), Total Carotene Content (TCC), water activity (Aw), acid value (AV), peroxide value (PV) and saponification value (SV). The results showed that: 38.00±1.00 – 48.83±1.61°C melting point, 1.46±0.00 RI, 1.18±0.06 mg/kg TCC, 0.4721±0.0176 Aw, 1.2162±0.1520 mg KOH/g AV, 9.6000±0.4000 g/g PV and 146.8040±18.0182 mg KOH/g SV, respectively. According to the results, RSF showed high industrial potential as cocoa butter replacement in chocolates and cosmetics production as the physicochemical properties of RSF is quite similar to cocoa butter.